2020
DOI: 10.1111/aogs.13878
|View full text |Cite
|
Sign up to set email alerts
|

Change in prevalence of major levator ani muscle defects from 6 weeks to 1 year postpartum, and maternal and obstetric risk factors: A longitudinal ultrasound study

Abstract: Introduction The present study aimed first to investigate the change in prevalence of major levator ani muscle (LAM) defects, also called avulsions, from 6 weeks to 1 year postpartum, and second to assess maternal and obstetric risk factors for having persistent major LAM defects/avulsions at 1 year postpartum. Material and methods This is a secondary analysis of data from a prospective cohort study including 300 nulliparous women at 17‐19 weeks of gestation. Major LAM defects were diagnosed at 6 weeks and 1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…It could be explained that we included both minor avulsions and hematomas, which are possibly disappeared in comparison to major injuries. A similar decrease in the incidence of LAM avulsion was also observed in several studies [18][19][20]. In this study, there was a non-significant correlation between levator ani avulsions and stress urinary incontinence which matches what have been observed by Delaney et al who found that visible defects in the levator ani muscle occurred with similar frequency in cases of SUI and controls [21].…”
Section: Discussionsupporting
confidence: 91%
“…It could be explained that we included both minor avulsions and hematomas, which are possibly disappeared in comparison to major injuries. A similar decrease in the incidence of LAM avulsion was also observed in several studies [18][19][20]. In this study, there was a non-significant correlation between levator ani avulsions and stress urinary incontinence which matches what have been observed by Delaney et al who found that visible defects in the levator ani muscle occurred with similar frequency in cases of SUI and controls [21].…”
Section: Discussionsupporting
confidence: 91%
“…Albrich et al [12] was excluded because presented a single case of LAM avulsion in one patient with FD. The estimated joint OR for VD vs. NVD was 2.02 (95% CI: 1.34-3.03), including the exploration of Halle et al [35] at 6 weeks postpartum (Fig. 2, Ref.…”
Section: Resultsmentioning
confidence: 98%
“…Five studies were retrospective and the rest prospective. The ultrasound examination was performed in most studies within 6 months after delivery [11][12][13][14][15][16][17]19,20,22,23,[25][26][27][28][29][30][31][32][33][34][35], though some performed an ultrasound examination only or also after this period [17,18,21,24,35,36]. Some papers included a small number of VDs [12,20,27] and FDs [12][13][14]27], a possible source of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Despite a study showing to 50% reduction in injuries observed by transperineal 3DUS comparing assessments of 6 weeks postpartum to 1 year after delivery in the same patient,[ 17 ] other authors have observed 15.2% rate of avulsion after 20 years of delivery. [ 18 ] We believe that the earlier the woman undergoes perineal rehabilitation after delivery, better she will recover.…”
Section: Discussionmentioning
confidence: 94%